Design and development of dual band Frequency Selective Surface (FSS) for reflector antenna system / Ainatul Afiqah Mohd Rashid - Mohd Rashid, Ainatul Afiqah (2017)
Frequency Selective Surface (FSS) are very thin layers which pass or reflect certain frequency of electromagnetic (EM) wave. Some specific designs of FSS have replaced bulky reflector systems in previous satelitte communication by single reflector system for different frequency bands of applications.